2019
DOI: 10.1177/0734282919848890
|View full text |Cite
|
Sign up to set email alerts
|

Development and Initial Validation of Cultural Competence Inventory–Preservice Teachers

Abstract: Despite the critical role of emotions in multicultural teacher education, no attempt has been made to develop an instrument including affect as a dimension in measuring cultural competence for preservice teachers. To bridge this gap, the present three-study research used three distinct samples of 456 preservice teachers to develop and estimate the reliability of scores and validity of inferences for Cultural Competence Inventory–Preservice Teachers (CCI-PT), an 18-item instrument including three subscales: emo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 42 publications
0
4
0
1
Order By: Relevance
“…In other words, second language teachers are ideally placed to mediate the successful socialization of migrant learners in the local school setting, as they tend to show higher levels of openness to new situations, empathy and understanding of the difficulties faced by multilingual learners ( Rokita-Jaśkow, 2023 ). Indeed, when working with a diverse student population, the appropriate use of “intercultural empathy and positive affect ensures effective communication” ( Yang et al, 2019 , p. 309) and supports the building of rapport between diverse students and teachers. Along the same lines, Hanna (2023) posits that disregarding the role of empathy as a core value for prospective teachers is linked to the difficulties in nurturing critical self-reflection among aspiring educators and raises questions about the adequacy of initial teacher education in preparing them for engaging effectively with migrant students.…”
Section: Introductionmentioning
confidence: 99%
“…In other words, second language teachers are ideally placed to mediate the successful socialization of migrant learners in the local school setting, as they tend to show higher levels of openness to new situations, empathy and understanding of the difficulties faced by multilingual learners ( Rokita-Jaśkow, 2023 ). Indeed, when working with a diverse student population, the appropriate use of “intercultural empathy and positive affect ensures effective communication” ( Yang et al, 2019 , p. 309) and supports the building of rapport between diverse students and teachers. Along the same lines, Hanna (2023) posits that disregarding the role of empathy as a core value for prospective teachers is linked to the difficulties in nurturing critical self-reflection among aspiring educators and raises questions about the adequacy of initial teacher education in preparing them for engaging effectively with migrant students.…”
Section: Introductionmentioning
confidence: 99%
“…The process of adapting the original CEQ to the Malaysian version of CEQ is similar to developing a new CEQ. Most of the previous psychometric new scale development studies have commonly shown that about 50% of the initial item pool was deleted during the validation process (Morgado et al, 2017;Yang et al, 2020). Therefore, this is a very common process, and the process of removing 14 items from the existing CEQ 36 items and four items from the 11 deep learning scale items in this study is acceptable.…”
Section: Factors Contributing Tomentioning
confidence: 86%
“…Preservice Teachers (CCIPT), elaborado y validado por Yang et al (2019). El inventario incluye 18 ítems, medidos en en consideración sus antecedentes culturales constituía un factor determinante para lograr un sólido rendimiento estudiantil y promover una mejora continua en la escuela.…”
Section: Conciencia Cultural Docente La Conciencia Cultural Docente F...unclassified